Wave propagation in anisotropic layered media (Archives of Mechanics - Test, 1996)
The propagation of time-harmonic waves in a continuously stratified anisotropic, viscoclastic layer bounded by two homogeneous anisotropic solid half-spaces, is studied analytically. A plane wave is assumed to impinge on the boundary of the layer, and the resulting field, inside and outside of the layer, is described according to the causality principle and formal wave-splitting. Reflection and transmission coefficients are derived for arbitrary angle of incidence, together with a formal expression of the wave field within the layer. A local reflectivity is defined as a function of the depth and used to obtain up and down-going modes in the layer. Reduction of the model to particular material symmetries allows for scalar fields whose properties generalize known results concerning the isotropic media. Numerical results are given to illustrate the method in the scalar case.